First Contact Management of Traumatic Hand Injuries - Jon Mikel Rementeria Vázquez; Dariana Martinez Marabotto; Brenda Leticia Rodríguez Bonachea; Carlos Rafael Martínez Hernández; David Martínez Rivera; Yazmín Pérez González; Pedro Suárez Loya; Zitlali Rios Ruiz (International Journal of Medical Science and Clinical Research Studies, 2024)
Performing a comprehensive history and physical examination is the first stage in treating any hand injury. This includes finding out the mechanism and timing of the injury, hand dominance, tetanus status, the patient's occupation, and baseline function. It is critical that the primary care physician oversee initial care in order to promote prompt healing and reduce long-term morbidity. It's crucial to identify injuries that need to be sent to hand surgeons as away. To enable prompt therapy of such an accident, direct phone communication between the on-call hand surgeon and the primary care physician is crucial.